Intellectual capital on organizational performance through the mediation of intrinsic motivation in Indonesian universities - Siti Fadhillah Nurazizah; Dwi Irawan; Ahmad Juanda; Sukma Uli Nuha (Journal of Accounting and Investment, 2024)
Research aims: This research examines how intellectual capital affects organizational performance in Indonesian universities, focusing on the mediating role of intrinsic motivation. It highlights the importance of intrinsic motivation in enhancing the influence of human capital, structural capital, and relational capital in improving organizational effectiveness.Design/Methodology/Approach: This quantitative study used survey data from 123 employees at top-ranked Indonesian universities by webometrics, selected via simple random sampling. The data were analyzed using variance-based structural equation modeling (SEM) with a Partial Least Squares (PLS) approach.Research findings: The findings of this study revealed a significant positive relationship between intellectual capital and organizational performance in Indonesian universities after being fully mediated by intrinsic motivation.Theoretical contribution/Originality: The novelty of this research exhibits how intrinsic motivation from well-organized Self Determination Theory (SDT) can mediate the influence of intellectual capital on organizational performance in higher education. The results of this study provide valuable insights for increasing intrinsic motivation in strengthening intellectual capital.Practitioner/Policy implication: This study's findings suggest that Indonesian university management and policymakers should focus on optimizing intellectual capital by fostering intrinsic motivation to enhance organizational performance.Research limitation/Implication: The limitation of this research is that there are no differences between private and state universities in examining the effect of intrinsic capital on organizational performance. It also only considers intrinsic motivation, ignoring extrinsic motivation. Future research should include extrinsic motivation and explore other intellectual capital indicators for a comprehensive understanding of organizational performance in Indonesian higher education.